Geotechnical Evaluation of Soils in Ammarah/Central Missan, Iraq (Journal of University of Babylon for Engineering Sciences, 2020)
Before any system of urban development is adopted, soil stratigraphy should be studied and geotechnical information should be determined. In the current study, fundamental geotechnical data for Ammarah city were collected and the inherent properties of soils and the manner of soil layers distribution were studied. Furthermore, problems involved in the soil of the study area were reviewed. Site investigations and laboratory testing showed that the area of interest is characterised by silt of different percentages distributed over the depth. Standard penetration and Vane shear test results revealed a horizontal discontinuity of soil layers. Investigating and reviewing soil problems showed that Ammarah soils are free of problems associated with sand dunes and high gypsum content. On the other hand, sabkha soil is widely distributed over the area due to salts and the shallow depth of water table.